Climate finance and charting a resilient future: Insights from CGIAR at COP 28 - Chilambe, Pedro; Kinyua, Ivy Wambui; Ouedraogo, Issa; Girvetz, Evan (2023)
This brief emphasizes CGIAR's commitment to integrating scientific research into the development of climate resilient strategies. It underlines the imperative of aligning these strategies with an intricate web of local, regional, and global climate finance objectives. Central to CGIAR's advocacy is the strategic utilization of scientific research in policy, innovative finance and investment decisions to augment and strategically direct climate finance for maximal impact.